2021
DOI: 10.7759/cureus.12480
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Profile of Hirschsprung’s Disease at a Tertiary Hospital in Bahrain

Abstract: Background Hirschsprung’s disease (HD) is a rare but important congenital pediatric disease of the colon, and its incidence varies widely between ethnic groups. Its incidence was first studied in Bahrain in 1980 using hospital-based data. Over a 16-month period, 10 cases were reported, representing a relatively high incidence rate: 1 per 4000 births. Even though the number of live births in Bahrain has increased dramatically over the last four decades (doubling from 10,000 to 20,000 per year), publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“… 3 , 6 This could be because there is a mild to moderate male preference in cases of Hirschsprung’s disease and anorectal malformation which were the most common causes of intestinal obstruction in our study. 20 , 21 Associated anomalies in our study were found to be 12.4%, which was very similar to the report of Mohammad et al, 3 while other studies have reported a higher prevalence. 22 , 23 The low prevalence of related congenital anomalies in this study can be due to some missed problems that will be revealed in post-neonatal investigations.…”
Section: Discussionsupporting
confidence: 91%
“… 3 , 6 This could be because there is a mild to moderate male preference in cases of Hirschsprung’s disease and anorectal malformation which were the most common causes of intestinal obstruction in our study. 20 , 21 Associated anomalies in our study were found to be 12.4%, which was very similar to the report of Mohammad et al, 3 while other studies have reported a higher prevalence. 22 , 23 The low prevalence of related congenital anomalies in this study can be due to some missed problems that will be revealed in post-neonatal investigations.…”
Section: Discussionsupporting
confidence: 91%
“…Male predominance was observed among the patients at a tertiary hospital in Bahrain, with a male-to-female ratio of 2.6:1. [8] This finding has also been reported in many other studies. [9–12]…”
Section: Discussionsupporting
confidence: 86%
“…The degree to which the absence of these ganglion cells extends varies between individuals. Failure of the migration of these ganglion cells results in the portion of the aganglionic segment of the colon failing to relax, resulting in a functional obstruction [ 5 ]. Hirschsprung disease presents mainly in the neonatal period, with 65% of the cases being diagnosed before the age of one month [ 6 ].…”
Section: Discussionmentioning
confidence: 99%